PERBANDINGAN PENGATURAN PENGELOLAAN EKOSISTEM PASCATAMBANG DI KEPULAUAN RIAU DAN JAMBI MANA YANG LEBIH BAIK - Verensia; Shelvi Rusdiana; Rufinus Hotmaulana Hutauruk (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2024)
This study aims to analyze the comparison of legal regulations on post-mining ecosystem management in Riau Islands and Jambi, with a focus on SDGs 15, which addresses the preservation of terrestrial ecosystems. The research questions explore how the legal framework for post-mining management is regulated in Indonesia and how it compares between the two provinces. The findings show that Riau Islands does not have a regional regulation that specifically governs post-mining management, while Jambi has a regional regulation addressing this issue. The research adopts a juridical-normative approach, analyzing applicable regulations at both the national and regional levels related to sustainable post-mining ecosystem management. The data sources include primary legal materials such as the Omnibus Law, the Mineral and Coal Law, the Environmental Protection and Management Law, the Post-Mining Reclamation Government Regulation, and other relevant regulations. Secondary data, including books, journals, and related studies, were also utilized. Data collection was carried out through library research, with data analysis using a juridical-qualitative method. The results of this study are expected to provide recommendations for improving post-mining ecosystem management regulations that support the preservation of sustainable terrestrial ecosystems in line with SDGs 15, particularly for provinces like Riau Islands, which lack specific regional regulations.